The BalticMAG catalog - Garcia, Sarahi; Pacheco-Valenciana, Armando; Dharamshi, Jennah; Delgado Zambrano, Luis Fernando; Andersson, Anders (Stockholm University, 2025)
This is a comprehensive catalog of species-cluster representative genomes. To make this catalog, we generated 527 metagenome-assembled genomes (MAGs) from 204 microbial model communities. Moreover, we binned 305 MAGs from the metagenomes corresponding to the samples from which we established the microbial model communities. To make the genomic catalog comprehensive, we added 771 MAGs from the publicly available metagenomes collected from the Baltic Sea (Alneberg et al., 2018, 2020). Altogether, the 1603 MAGs were dereplicated into 701 species-clusters (average nucleotide identity - ANI ≥ 95%), which form the Baltic Sea genomic catalog (BalticMAG catalog).

In this Figshare, we share all 701 species-cluster representative genomes. Moreover, you will find a table with metadata for the genomes.
Keywords: Microbial ecology; Medical and Health Sciences; Medicin och hälsovetenskap; Ecology; Ekologi